Stress experienced by adolescents in the context of the analysis of demographic variables - Alifanovienė, Daiva; Vaitkevičienė, Asta; Šapelytė, Odeta; Šarauskienė, Danutė (Special Education, 2016)
The article deals with the peculiarities of stress experienced by adolescents in the context of the analysis of social, demographic variables. Research data enabled to identify stressful situations and negative emotions which are experienced by adolescents depending on their sex, age. Respondents’ data were analysed using descriptive and mathematical statistics methods. It was found that adolescents found themselves in stressful situations and experienced negative emotions. Senior age female adolescents find themselves in such situations most often, the place of residence is little significant for adolescents’ stressful experiences, while social environment of the school is to be considered a strong stressogenic factor.